Prevalence of H pylori in obese attending Obesity therapy Unit - Hana, Mumtaz K (AL-Kindy College Medical Journal, 2019)
Background: Obesity is an increasing health problem in developed countries and has grown into a major global epidemic. Recent studies suggested colonization of the stomach by Hpylori might affect gastric expression of appetite- and satiety-related hormone and patients cured of H pylori infection gained weight. Obesity and Helicobacter pylori (H. pylori) are important because of the problems they lead and their frequency of occurrence. Objectives: To find out the prevalence of H. pylori infection in obese. Type of the study:A cross-sectional study Methods: A total of 32 obese female admitted to the study. Body mass indices (BMI) of all subjects were calculated H. pylori positivity were studied. Results: The age range of the obese was (20-59) and the BMI (was 25-55 kg/m²). 26 obese (81.25%) were H pylori positive, and all obese above 45 were H pylori positive. Conclusions: Obesity and h pylori are closely associated and the prevalence of h pylori increased with obesity. We consider that H. pylori infection can be a risk factor for obesity and almost all obese patients above 45 years were sero positive. However, further studies evaluating more subjects are required. And we need to do national survey about h pylori prevalence in our community